A scoping analysis of the aspects of primary healthcare physician job satisfaction: facets relevant to the Indonesian system - Maharani, Chatila; Marx, Michael; Loukanova, Svetla (Human resources for health, 2019)
Background: Although there is extensive literature on the different aspects of physician job satisfaction worldwide, existing questionnaires used to measure job satisfaction in developed countries (e.g., the Job Satisfaction Scale) do not capture the aspects specific to Indonesian primary healthcare physicians. This is especially true considering the 2014 healthcare system reform, which led to the implementation of a national social health insurance scheme in Indonesia that has significantly changed the working conditions of physicians. Therefore, the current study aimed to identify aspects of primary care physician job satisfaction featured in published literature and determine those most suitable for measuring physician job satisfaction in light of Indonesia’s recent reforms.Methods: A scoping literature review of full-text articles published in English between 2006 and 2015 was conducted using the PubMed, Psycinfo, and Web of Science databases. All aspects of primary care physician job satisfaction included in these studies were identified and classified. We then selected aspects mentioned in more than 5% of the reviewed papers and identified those most relevant to the post-reform Indonesian context.Results: A total of 440 articles were reviewed, from which 23 aspects of physicians’ job satisfaction were extracted. Sixteen aspects were deemed relevant to the current Indonesian system: physical working conditions, overall job satisfaction, patient care/treatment, referral systems, relationships with colleagues, financial aspects, workload, time of work, recognition for good work, autonomy, opportunity to use abilities, relationships with patients, their families, and community, primary healthcare facilities’ organization and management style, medical education, healthcare systems, and communication with health insurers.Conclusion: Considering the recent reforms of the Indonesian healthcare system, existing tools for measuring job satisfaction among physicians must be revised. Future research should focus on the development and validation of new measures of physician job satisfaction based on the aspects identified in this study.
Gesehen am 04.10.2019